Challenges in the Management of Massive Carotid Body Tumor - Oluwapelumi Olusoga-Peters; Moses Ayodele Akinola; John Ifeanyi Nwadiokwu; Florence Oguntade (Case Reports in Otolaryngology)
The carotid body paraganglioma is a rare benign neoplasm arising from the chemoreceptor cells of the carotid bulb. The carotid body has the largest collection of paraganglia in the head and neck with 60–70% of head and neck paraganglioma. Paraganglia are clusters of cells originating from the neural crest with histological and cytochemical characteristics of neuroendocrine cells. It is mostly asymptomatic in early presentation but become symptomatic and difficult to manage when the tumor is large. We present a case of a 26-year-old male who presented with a painless, pulsatile, progressively increasing left lateral neck swelling of 5 years duration with Shamblin IIIa. The diagnosis of the tumor was confirmed based on clinical features, histology, and radiological findings. We had difficult surgical dissection of the tumor with neurovascular damage.